BIOMASS CHARACTERISTICS AND CARBON STOCK KATINGAN PEAT SWAMP FOREST, CENTRAL KALIMANTAN - Auliadina Nasution, Rahmi
Degradation of peat swamp forest is one of the source that contributes to the increase in CO2 into the atmosphere, hence increasing greenhouse gas concentration. Peat swamp forest restoration activities need to be carried out to restore the function of peatlands as the main carbon sink. Katingan peat swamp forest is one of the degraded peat swamp forests in Central Kalimantan which requires restoration to restore it’s main functions. This study aims to examine the characteristics of the stands biomass and estimate the carbon stock in various carbon pools Katingan peat swamp forest (KPSF). This research using vegetation and peat secondary data from Katingan peat swamp forest published by Center for International Forestry Research (CIFOR). Data were collected by CIFOR researchers in July and October 2015 in the KPSF area, Central Kalimantan. The calculated carbon stock comes from three carbon pools, namely, above ground carbon, below ground carbon, and peat carbon. The research was conducted in two plots (north and south) each measuring 100m x 100m divided into 25 subplots measuring 20m x 20m. In all sub plots, local names and tree diameters were recorded (min 2.9 cm). Soil sampling was carried out on 5 sub plots along 5 cm at the midpoint of systematic depth (interval 0-20 cm, 20-50 cm, 50-100 cm, 100-200 cm, 200-300 cm, 300-400 cm,> 400 cm , or until it reaches the mineral layer). The results showed that the above-ground biomass value of the Katingan peat swamp forest stands was 124.69 ton / ha, with the following characteristics. Small trees diameter <50 cm contributed 90.06% of the total biomass, and species with wood density > 0.48 contributed 79.83% of the total biomass. The total carbon storage of Katingan Peat Swamp Forest was 1,907.45 ton C / ha, consisting of live plant carbon storage of 71.70 ton C / ha and peat carbon storage of 1,835.75 ton C / ha. The largest carbon proportion is found in the peat carbon pool which contributed 96.24% of the total carbon storage.